praktika Studi Deskriptif Penerapan Pemuridan Di Komunitas Remaja - Yogi Santoso; Kalis Stevanus; Fianus Tandiongan; Gidion Gidion (CARAKA: Jurnal Teologi Biblika dan Praktika, 2022)
Discipleship is very important in Christianity. Discipleship is a mandate of Christ which is parallel to the mandate of evangelism. Every believer needs to be discipled to be matured toward Christlikeness. The purpose of this study was to describe the level of discipleship implementation in the youth community of GBT Alfa Omega Semarang. To answer the research objectives, a literature approach was used to explain the theoretical study of discipleship and also used a descriptive quantitative method to find out the numerical effectiveness of the application of discipleship in the youth community. The research results obtained by 84% or interpreted in the very good category.